2018
DOI: 10.3390/ijerph15020263
|View full text |Cite
|
Sign up to set email alerts
|

Fat Mass Index and Body Mass Index Affect Peak Metabolic Equivalent Negatively during Exercise Test among Children and Adolescents in Taiwan

Abstract: Peak metabolic equivalent (MET) is the most reliable indicator of cardiorespiratory fitness (CRF). The aim of this study was to examine the association between CRF indicated by peak MET and body mass index (BMI) or fat mass index (FMI) in Taiwanese children and adolescents (C-A). Data of 638 C-A aged 10–18 that received symptom-limited treadmill exercise testing was analyzed. Anthropometry-body composition was measured by vector bioelectrical impedance analysis. BMI was defined as body weight (kg)/body height … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
8
1
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 29 publications
6
8
1
3
Order By: Relevance
“…Furthermore, it is reported (e.g., Ostojic et al, 2011 ; Esmaeilzadeh et al, 2013 ; Tuan et al, 2018 ) that there is a negative correlation between central obesity (WC and WHtR) and cardiovascular fitness which is in line with our findings. Those children with higher central obesity have shown to have lower CRF estimated by using the maximal multistage 20 m shuttle run test.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Furthermore, it is reported (e.g., Ostojic et al, 2011 ; Esmaeilzadeh et al, 2013 ; Tuan et al, 2018 ) that there is a negative correlation between central obesity (WC and WHtR) and cardiovascular fitness which is in line with our findings. Those children with higher central obesity have shown to have lower CRF estimated by using the maximal multistage 20 m shuttle run test.…”
Section: Discussionsupporting
confidence: 93%
“…In the current study, girls had lower values in obesity indices than boys, which was in accordance with some previous studies ( Ortega et al, 2007 ; Gomes et al, 2014 , 2015 ; World Health Organization, 2017 ; Tuan et al, 2018 ) and at odds with others ( Al-Nakeeb et al, 2007 ; Ostojic et al, 2011 ; Dencker et al, 2012 ). Lower obesity indices among girls in this age range may not necessarily pertain to their healthier lifestyle as our results showed that girls had a lower level of PA and CRF compared to boys across all age groups with a more prominent difference in age of 12 and 13.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…When compared to other, similar obese adolescents, the PWS patient showed much declined aerobic fitness (See Table 3). BMI was significantly negatively associated with both AT MET and peak MET [9]. However, the PWS patient still showed much declined AT MET and peak MET even though his age, gender and BMI were similar to the control group.…”
Section: Discussionmentioning
confidence: 76%